2022
DOI: 10.3389/fimmu.2022.939523
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of an anoikis-associated gene signature to predict clinical character, stemness, IDH mutation, and immune filtration in glioblastoma

Abstract: BackgroundGlioblastoma (GBM) is the most prominent and aggressive primary brain tumor in adults. Anoikis is a specific form of programmed cell death that plays a key role in tumor invasion and metastasis. The presence of anti-anoikis factors is associated with tumor aggressiveness and drug resistance.MethodsThe non-negative matrix factorization algorithm was used for effective dimension reduction for integrated datasets. Differences in the tumor microenvironment (TME), stemness indices, and clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 60 publications
2
53
0
1
Order By: Relevance
“…HCC is a highly life-threatening malignancy, and effective predictive biomarkers of HCC are still lacking. Recently, an increasing number of studies have demonstrated alterations of anoikis regulators and their significant role in tumorigenesis and progression in various malignancies, including lung cancer, prostate cancer, breast cancer and glioblastoma ( Jin et al, 2018 ; Tajbakhsh et al, 2019 ; Du et al, 2021 ; Sun et al, 2022 ; Yu et al, 2022 ). However, the underlying mechanisms and prognostic value of dysregulated anoikis-related genes in HCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is a highly life-threatening malignancy, and effective predictive biomarkers of HCC are still lacking. Recently, an increasing number of studies have demonstrated alterations of anoikis regulators and their significant role in tumorigenesis and progression in various malignancies, including lung cancer, prostate cancer, breast cancer and glioblastoma ( Jin et al, 2018 ; Tajbakhsh et al, 2019 ; Du et al, 2021 ; Sun et al, 2022 ; Yu et al, 2022 ). However, the underlying mechanisms and prognostic value of dysregulated anoikis-related genes in HCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In addition, ARGs have been proven to be associated with prognosis in several tumors. 11 , 12 , 13 However, the comprehensive analyses of the implications of anoikis in LUAD are still scarce. Therefore, identification of the predominant genes related to anoikis with prognostic significance in LUAD is vital.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by D'Amato et al, TDO2 was found as an attractive factor to facilitate anoikis resistance in triple‐negative breast cancer 10 . In addition, ARGs have been proven to be associated with prognosis in several tumors 11–13 . However, the comprehensive analyses of the implications of anoikis in LUAD are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Anoikis, as a programmed cell death, is a potential barrier to cancer cell metastasis. Previous studies have pointed that the epithelial or endothelial cells detached from extracellular matrix (ECM) succumb to classical apoptosis commonly known as anoikis ( Chi et al, 2022 ; Sun et al, 2022 ). Evasion from apoptosis is one of the essential changes in the malignant transformation of cells.…”
Section: Introductionmentioning
confidence: 99%